Pancasila State as Dar al-‘Ahdi (National Consensus) Based on Muhammadiyah - Yulia Qamariyanti; Erlina, Erlina; Muhammad Fikri Aufa (CV. Strata Persada Academia, 2024)
The founders of the nation based their philosophy, known as Pancasila, on the religious and cultural diversity of the Indonesian people. It is the foundation of the Unitary State of the Republic of Indonesia. The purpose of this research is to analyse and present a summary of Muhammadiyah's dar al-'ahdi (national consensus) interpretation of the Pancasila State concept. One of the biggest social-community organisations, Muhammadiyah, sees Pancasila as a dar al-'ahdi (national consensus) that was established in the Muhammadiyah Muktamar decision tanfidz of 2015. Because Muhammadiyah holds the belief that Pancasila must occupy the highest position in the life of the nation and state with the concept of Pancasila state darul al-'ahdi wa shahadah, this concept was developed. Muhammadiyah has observed Pancasila being strengthened and is dedicated to doing so as well as interpreting the diversity that has been reflected in the faith and conviction of Muhammadiyah life's values. The Pancasila as Dar al-'Ahdi wa al-Syahadah-based Indonesian state already has a solid ideological foundation.